Using single molecule fluorescence to study substrate recognition by a structure-specific 5’ nuclease - Rashid, Fahad (2018)
Nucleases are integral to all DNA processing pathways. The exact nature of substrate recognition and enzymatic specificity in structure-specific nucleases that are involved in DNA replication, repair and recombination has been under intensive debate. The nucleases that rely on the contours of their substrates, such as 5’ nucleases, hold a distinctive place in this debate. How this seemingly blind recognition takes place with immense discrimination is a thought-provoking question. Pertinent to this question is the observation that even minor variations in the substrate provoke extreme catalytic variance. Increasing structural evidence from 5’ nucleases and other structure-specific nuclease families suggest a common theme of substrate recognition involving distortion of the substrate to orient it for catalysis and protein ordering to assemble active sites. Using three single-molecule (sm)FRET approaches of temporal resolution from milliseconds to sub-milliseconds, along with various supporting techniques, I decoded a highly sophisticated mechanism that show how DNA bending and protein ordering control the catalytic selectivity in the prototypic system human Flap Endonuclease 1 (FEN1). Our results are consistent with a mutual induced-fit mechanism, with the protein bending the DNA and the DNA inducing a protein-conformational change, as opposed to functional or conformational selection mechanism. Furthermore, we show that FEN1 incision on the cognate substrate occurs with high efficiency and without missed opportunity. However, when FEN1 encounters substrates that vary in their physical attributes to the cognate substrate, cleavage happens after multiple trials During the course of my work on FEN1, I found a novel photophysical phenomena of protein-induced fluorescence quenching (PIFQ) of cyanine dyes, which is the opposite phenomenon of the well-known protein-induced fluorescence enhancement (PIFE). Our observation and characterization of PIFQ led us to further investigate the general mechanism of fluorescence modulation and how the initial fluorescence state of the DNA-dye complex plays a fundamental role in setting up the stage for the subsequent modulation by protein binding. Within this paradigm, we propose that enhancement and quenching of fluorescence upon protein binding are simply two different faces of the same process. Our observations and correlations eliminate the current inconvenient arbitrary nature of fluorescence modulation experimental design.